Given:
![f(x)=3x^3+7x^2-14x+24](https://img.qammunity.org/2023/formulas/mathematics/college/kfrneazoxue6brhexhwdzqspx3nkvt2hpj.png)
Let's use synthetic division to find the zeros.
Given: x = -4, 3
Let's first find f(-4) and f(-3).
Substitute -4 for x and solve for f(-4):
![\begin{gathered} f(-4)=3(-4)^3+7(-4)^2-14(-4)+24 \\ \\ f(-4)=-192+112+56+24 \\ \\ f(-4)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/31q8hjid8lyqdz0zyudmasb9ee0pngdxl8.png)
Since f(-4) = 0, it means that -4 is a zero of the function.
Also let's solve for f(-3):
![\begin{gathered} f(3)=3(3)^3+7(3)^2-14(3)+24 \\ \\ f(3)=81+63-42+24 \\ \\ f(3)=126 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/q0lhshj7eg7b5kmde0zx1t6znxorhohig3.png)
-3 is not a zero.
Now, let's perform a synthetic division using the known zero: x = -4.
To divide, set the numbers representing the dividend and the divisor in the long division like method then perform the division.
We have:
The numbers below the division line represents the quotient except the last number which is the remainder.
Thus, we have:
![f(x)=(x+4)(3x^2-5x+6)](https://img.qammunity.org/2023/formulas/mathematics/college/hoa75tifbqzzkl3vthv9wfib4sjpde0zh9.png)
The expression cannot be factored any further.
Since it cannot be factored any further, we have only one zero which is:
x = -4.
Therefore, the number -4 is a zero of the polynomial function because f(-4) = 0 and the number 3 is not a zero of the function because f(3) = 126.
• ANSWER:
A. The number -4 is a zero of the polynomial function because f(-4) = 0 and the number 3 is not a zero of the function because f(3) = 126.